Modification of Kaplan Turbine with Variation of Guide Angle (Guide Vanes) to Generate Electric Power - Amin Jakfar; Misbakhul Fatah; Anauta Lungiding Angga R (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
Hydroelectric power plant is renewable electrical energy that is needed at this time. One of the hydropower plants that has been designed is the Kaplan turbine, which is intended for the Geladak Kenong river, Pamekasan. The turbine is designed to produce 1000 Watts of power. In the manufacture of the turbine, several variations have been carried out, namely the diameter of the turbine blades, the angle of the turbine blades and the height of the draft tube. However, the power generated is relatively small, which is 416.89 Watts. In this modification, Kaplan turbines will be made with variations in Guide Vanes angles of 15⁰, 25⁰, 35⁰ and 45⁰. Its working principle is optimizing water energy to improve Turbine performance. The method used in this study is to vary the angle of the Guide Vanes which can affect the power generated. The results of the Kaplan Turbine test, the highest power of 521.79 Watt, occurred at a Guide Vanes angle of 25⁰ with a discharge of 0.0152 m3/s and a rotation of 466 rpm. Pembangkit listrik tenaga air (PLTA) merupakan energi listrik terbarukan yang sangat dibutuhkan pada saat ini. Salah satu PLTA yang telah dirancang yaitu turbin Kaplan yang diperuntukkan di sungai Geladak Kenong Pamekasan. Turbin tersebut dirancang untuk dapat menghasilkan daya sebesar 1000 Watt. Dalam pembuatan turbin tersebut telah dilakukan pengujian dengan beberapa variasi yaitu diameter sudu tubin, sudut sudu turbin dan ketinggian draft tube. Namun daya yang dihasilkan relatif kecil yaitu sebesar 416,89 Watt. Pada modifikasi ini akan dibuat Turbin Kaplan dengan variasi sudut Guide Vanes 15⁰, 25⁰, 35⁰ dan 45⁰. Prinsip kerjanya mengoptimalkan energi air untuk meningkatkan kinerja Turbin. Metode yang digunakan dalam penelitian ini ialah memvariasi sudut Guide Vanes yang dapat mempengaruhi daya yang dihasilkan. Hasil dari pengujian Turbin Kaplan, daya tertinggi sebesar 521,79 Watt, terjadi pada sudut Guide Vanes 25⁰ dengan debit 0.0152 m3/s dan putaran 466 rpm.